PENDAMPINGAN DAN PENGEMBANGAN UMKM WARUNG PONDOK PESONA SEBAGAI UPAYA UNTUK MENINGKATKAN EKONOMI KELUARGA - Yana Fajar Raihan; Moh. Fathkul Anam; Aril Dwi Rangga Ardiyansah; Adelia Ika Damayanti (Jurnal Pengabdian kepada Masyarakat Cahaya Negeriku, 2025)
Background: Micro, Small, and Medium Enterprises, or MSMEs, play a crucial role in driving the Indonesian economy. There are 64.2 million MSMEs operating and employing 97% of the national workforce (Ministry of Cooperatives and SMEs 2018). However, many MSMEs still face challenges and challenges in managing their businesses. One of the MSMEs, namely the MSME "Warung Pondok Pesona" owned by Mrs. Yati who is still experiencing problems such as not having a business name and logo, lack of MSME branding, lack of information about the business, MSME owners not yet doing financial bookkeeping and lack of optimization of the cleanliness of the MSME premises.Objective: This mentoring program aims to help the MSME "Warung Pondok Pesona" owned by Mrs. Yati to improve and enhance the quality of the business, and aims to improve the family economy through business income. Method: This mentoring activity was carried out in three stages, namely pre-implementation (observation), direct mentoring and evaluation. The methods implemented included field surveys, implementation of program solutions based on problems and monitoring program implementation. Results: The KKU mentoring program was successfully implemented with several outputs that were in line with MSME problems, namely helping to provide MSME names and product logos, creating banners as MSME branding, installing MSME directional signs as promotional media, providing financial management education and providing financial record books and providing trash bins as an effort to optimize MSME cleanliness. All programs have been successfully implemented well within one month. Conclusion: Activities The mentoring program for the "Warung Pondok Pesona" MSME through the KKU program has been completed. It is expected to support business improvement and improve family economic well-being.